The Macroeconomic Effects of ESAF-Supported Programs : Revisiting Some Methodological Issues - Schadler, Susan (IMF Working Papers; Working Paper, 1995)
This paper examines whether ESAF-supported programs during 1986-91 had significant independent effects on growth, inflation and the external debt service ratio. Econometric estimates of the Generalized Evaluation Estimator (GEE) identify statistically significant beneficial effects on output growth and the debt service ratio but no effects on inflation. The robustness of these estimates is also examined. Diagnostic tests cast doubt on the applicability of the GEE framework to the ESAF-eligible countries, and the results obtained using it.